UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU MATA PELAJARAN EKONOMI DALAM PROSES PEMBELAJARAN - Henny Indrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
This study aims to: (1) describe the professional competence of Economic’s teachers in thelearning process, and (2) finding the professional competence of Economic’s teachers’ efforts. Thesamples were teachers of Economics and head of public and private high schools in the district MerantiIslands, purposively selected based on school accreditation. Data analysis used descriptive qualitative.The study found: (1) In general, the professional competence of Economic’s teachers in Meranti IslandsRegency were low, (2) There are two efforts made to improve the professional competence ofEconomic’s teachers in Meranti Islands Regency, namely the efforts of teachers and principals efforts.Efforts are made teachers are: follow MGMPs (Subject Teachers Council), following the upgrading /training, attend courses, gain knowledge through mass media or electronics, and professional improvementthrough self study. Efforts are made principals include: conduct supervision, conduct and or assigningteachers to participate in training, provision of adequate education facilities, motivated teachers makescientific work, rewards, and held a school meeting.Key words: professional competence, teachers of Economics, learning process